Factors Influencing Farmers' Fertilizer Practices On Irrigation Schemes In The Central Parts Of South Africa - Nell, Frederikus, Jacobus, Johannes (Central University of Technology, Free State, 2019)
Fertilizer containing macro and micro elements forms the basis of a good yield and should be applied in correct quantities. Fertilizer should be applied at the correct physiological growth stage of the plant. Of further importance is the cost associated with fertilizers, since it makes a meaningful contribution to the total input cost per hectare of crop cultivation. A common problem is that some farmers do not have sufficient knowledge of the fertilisation requirements of plants to make an informed decision. This makes the farmer entirely dependent on the recommendations of fertilizer advisors, who are also the salesmen, regarding the types and quantities of fertilizers (macro and micro elements) to be applied. As a result of the ignorance or skepticism of farmers, this may lead to under- or overapplication of inorganic fertilizers. The overall objective of this study is to determine the fertilisation practices as applied by farmers in the irrigation areas of the Jacobsdal, Prieska, Vaalharts and Douglas regions in the central parts of South Africa. The study consist of four main objectives, namely: 1. to study the behavior of the farmers regarding their fertilizer management practices; 2. to study the fertilizer salesmen's behaviour and their influence on the farmers’ fertilizer practices; 3. To determine the fertilizer companies’ marketing strategies and how they influence the farmers’ decision making; and 4. To determine the level of variations in soil analyses results and recommendations between different laboratories. Various sub-objectives were formulated within each objective. A stratified random sample was used to select the respondents for the study in order to ensure the representability of all groups. To satisfy the first three objectives of the study, three questionnaires were constructed and consequently filled via personal interviews with these farmers, fertilizer agents (salespersons) and fertilizer companies as respective respondents. Both Excel and SPSS were used to analyse the data while various statistical tests were used to identify trends and correlations within the data. Regarding the farmer’s behaviour concerning fertilizer management (the 1st objective), significant differences were found between some of the four irrigation (sample) areas for the average nitrogen input cost per hectare for early planting (p = 0.0026) and late planting (p < 0.0001). As far as differences in nitrogen cost based on the farm size are concerned, no significant differences could be found between the nitrogen input cost between smaller and larger farm groups. No significant differences were found in the phosphate and potassium input costs per hectare between the four sample areas. However, a significant difference was found between the small and larger farms at Vaalharts (p < 0.0001) vis-à-vis potassium costs per hectare for early planting. Concerning the average cost for micro elements per hectare, statistical differences was found for an early plant (p = 0.0226), as opposed to a late plant (p < 0.0001) between some of the areas. When considering the total input cost of fertilizer per hectare, the Douglas sample group was significantly higher than Vaalharts and Prieska respectively. It was found that the size of the farming unit makes no significant difference as far as the total input cost of fertilizer per hectare is concerned. The only exception was with the Prieska sample group that showed a significant difference in packaging preference of fertilizer bags, i.e. the larger farmers prefer to use large bags and bulk fertilizer, while the small farmers prefer small (50kg) bags that can be moved by hand. The respondents were divided into three groups according to their highest academic qualification, as well as according to farming experience. No significant differences were found between these education and experience groups when considering the various fertilizer practices and assessment of the fertilizer salesmen. The only exception was the significantly better (p = 0.0059) ability of the group with tertiary agricultural qualifications to understand the soil analysis report and verify the fertilizer recommendation made by the fertilizer agent. None of the other demographics (e.g. age, experience and gender) play any significant role in farmers’ fertilizer practices. It is recommended that farmers must apply different strategies to control or manipulate the price of their inputs without compromising yield, soil fertility and the long-term sustainability of the farming unit. These strategies will differ between farmers due to every farm’s unique situation, for example economies of scale and the financial position (liquidity) of the farming business. Regarding the profile of the fertilizer salesman, it was found that when the financial position of the farming business (i.e. restricted or surplus funding and target yield) is disclosed to the fertilizer agent, significant differences were found in the quantities of nitrogen, phosphate and potassium that were recommended by the sales representative, especially reduced N and P when funds are limited, while significant higher application rates of N, P and K were made when funding is no limitation and nutrient reserves need to be improved. It is recommended that a farmer must select the fertilizer salesperson with extreme prudence. This person provides valuable information that will assist the farmer to make decisions that will have a huge impact on the financial success of the farming business, while it will also influence soil fertility and contribute to the long-term sustainability of the farm. Regarding the 3rd objective, whereby the marketing strategies of the fertilizer companies were perused, the farmer should always bear in mind that a fertilizer company’s mail goal is maximum profit and not the welfare of the farmer as individual. They all sell basically the same product and farmers must keep in mind that the company’s agronomic services (for example soil sampling and cost of analysis), may be costly as it is then integrated into or added to the price of the purchased fertilizers. Alternative independent agronomic services are available and the cost thereof can be offset by purchasing much cheaper fertilizers, resulting in a much lower total cost. The 4th objective of the study was to investigated variations in soil analysis reports or results amongst four different laboratories in South Africa. A large soil sample was taken under supervision of an independent agronomist, then thoroughly mixed and divided into forty (40) sub-samples. These were sent to four different soil laboratories one week apart in three different batches. The laboratories were unaware that the three batches were from the same source. By using an ANOVA, the results of the soil samples were statistically analysed and meaningful differences (p < 0,05) were found in the analysed levels of macro-elements (N, P and K) between laboratories as well as between different batches within each laboratory. Less variation was found with regard to microelements where significant differences were only found in the analysed copper (Cu) and boron (B) contents of some labs. The study results indicated that meaningful variations may occur between different laboratories, although it was found that some laboratories have less or almost no variation between the different batches that were analysed. A laboratory with the most consistent results must thus be used in order for the farmer to create a reliable record of the trends in soil fertility status of the farming unit.
Dissertation